"أثر الإبداع الإداري على أداء الموار البشرية-دراسة حالة مصحة الرمال لولاية الوادي " - عبد الخالق, توارس; خزاني, بيسي (unuversity of eloued- جامعة الوادي, 2023)
"ملخص تهدف هذه الدراسة، إلى التعرف على أثر الإبداع الإداري على أداء الموارد البشرية وذلك من خلال قياس مستوى الابداع والأداء في المؤسسة الصحية الخاصة مصحة الرمال بولاية الوادي ، إضافة الى اختبار العلاقة بين عناصر الابداع الإداري و عناصرالأداء للمورد البشري . ثم مقارنة النتائج المتحصل عليها للخروج باستنتاجات يمكن أن يستفاد منها في تطوير الأساليب الإدارية، وتحقيق مستوى عال من الابداع لدى عمال المؤسسات الصحية الخاصة ، وبالتالي مستوى مرتفع من الأداء ولتحقيق هذا الهدف تم اعتماد المنهج الوصفي التحليلي في الجزءالنظري ومنهج دراسة الحالة في الجزء العملي. ثم تم تطوير استبيان وتوزيعه على عينة الدراسة، التي تم اختيارها من مجتمع مكون من عدد من العاملين في المؤسسة محل الدراسة ، بطريقة العينة العشوائية، وزعت عليهم 35استبانة، استرجع منها 31. وبعد تبويبها وترتيبها، بإدخالها إلى برنامج التحليل الإحصائي ،SPSS V.25تم تحليل محاور الدراسة واختبار فرضياتها، بوسائل التحليل الاحصائي الوصفي و الاستدلالي وقد تم التوصل إلى مجموعة من النتائج، من أهمها: - الموارد البشرية العاملة بمصحة الرمال بولاية الوادي يمتلكون جميع القدرات المميـزة للشخـصية المبدعـةبدرجةعالية. - المتغيرات الإدارية ( الإبداع الأداء) قيد الدراسة تساهم بدرجات متفاوتة في توفير المناخ الإبداعي. - واقع الإبداع الإداري بمصحة الرمال بولاية الوادي بشكل عام ضعيف . - عملية تقويم الأداء بالقطاع الخاص عموما لا تتم بشكل صحيح وفعال بما يخدم المورد البشري والإ دارة معاً. وأهم توصيات الدراسة : - إنشاء إدارة حاضنة للإبداع أو إنشاء ما يسمى بنك الأفكار. - وضع إستراتيجية مبنية على معايير دقيقة للكشف عن المبدعين والموهوبين. - إنشاء نظام تقويم الأداء يضمن معايير تقويم موضوعية وواضحة، تكفـل اطـلاع الموارد البشرية على نتائج التقويم." "Résumé This study aims to identify the impact of administrative creativity on the performance of human resources by measuring the level of creativity and performance in the private health institution, Al-Rimal Clinic in El-Oued state, and to identify the extent to which it uses administrative methods that achieve and enhance creativity, in addition to testing the relationship between the elements of administrative creativity and the elements of performance of the resource human.. To achieve this goal, the analytical descriptive approach was adopted in the theoretical part and the case study approach in the practical part. Then a questionnaire was developed and distributed to the study sample, which was chosen from a community consisting of a number of employees in the institution under study, using a random sample method. 35 questionnaires were distributed to them, 31 of which were retrieved. After classifying and arranging them, by entering them into the SPSS V.25 statistical analysis program, the study axes were analyzed and its hypotheses tested, by means of descriptive and inferential statistical analysis. A number of results were reached, the most important of which are: - The human resources working at Al-Rimal Sanitarium in Al-Wadi state possess all the distinctive capabilities of a highly creative personality. - Administrative variables (creativity, performance) under study contribute to varying degrees in providing a creative climate. - The reality of administrative creativity in Al-Rimal Sanitarium in Al-Wadi state is generally weak. - The process of evaluating performance in the private sector in general is not done properly and effectively in a manner that serves the employees and management together. The most important recommendations of the study: - Establishing an incubator department for creativity or establishing what is called an Idea Bank. - Developing a strategy based on accurate criteria to detect creative and talented people. - Activating the incentive system based on professional foundations and standards that include excellence and creativity in performance and rewarding creators. Establishing a performance appraisal system that includes objective and clear evaluation criteria, ensuring that the employee is informed of the evaluation results."
Keywords: الابداع الإداري، أداء الموارد البشرية ،الاصالة، المرونة، الطلاقة، قبول المخاطرة، الحساسية للمشكلات، التحليل والربط ،الاصرار والمثابرة; administrative creativity, human resource performance, human resource management, originality, flexibility, fluency, acceptance of risk, sensitivity to problems, analysis and connection, persistence and perseverance.